Penerapan Model Pembelajaran Picture And Picture Dalam Meningkatkan Hasil Belajar Seni Budaya - Ratdriani, Ratdriani (JURNAL PENA EDUKASI, 2018)
Abstract: This study aims to determine the improvement of learning outcomes of Art Culture students on the material Simple Musical Instruments in class VII.1 SMP Negeri 1 Kisaran academic year 2017/2018. The subjects of this study are students of class VII.1 SMP Negeri 1 Kisaran as many as 32 people. The object of this research is the result of student learning using Picture and Picture learning model in Simple Music Material material. The research instrument used is multiple choice test and observation. Based on the research results obtained pretest average value of 48.33. After giving the action on the first cycle there were 15 people (46.88%) of the 32 students who achieved the minimum mastery criteria with an average score of 69.37. In cycle II there were 30 people (93.75%) who achieved the minimum mastery criteria with an average score of 85.27. Increased student learning outcomes by 41.66%. Student learning activities during the learning process show a better improvement. Because it has fulfilled classical learning completeness and increased from cycle I to cycle II it can be concluded that with the use of Picture and Picture learning model can improve students' learning achievement of Art Culture on Simple Musical Instrument material in class VII.1 SMP Negeri 1 Kisaran academic year 2017/2018. Keywords: picture and picture, simple musical instruments. Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar Seni Budaya siswa pada materi Alat Musik Sederhana di kelas VII.1 SMP Negeri 1 Kisaran Tahun Pelajaran 2017/2018. Subjek penelitian ini adalah siswa kelas VII.1 SMP Negeri 1 Kisaran sebanyak 32 orang. Objek penelitian ini adalah hasil belajar siswa menggunakan model pembelajaran Picture and Picture pada materi Alat Musik Sederhana. Instrumen penelitian yang digunakan adalah tes berbentuk pilihan ganda dan observasi. Berdasarkan hasil penelitian diperoleh nilai rata-rata pretes sebesar 48,33. Setelah pemberian tindakan pada siklus I terdapat 15 orang (46,88%) dari 32 orang siswa yang mencapai kriteria ketuntasan minimum dengan nilai rata-rata 69,37. Pada siklus II terdapat 30 orang (93,75%) yang mencapai kriteria ketuntasan minimum dengan nilai rata-rata 85,27. Peningkatan hasil belajar siswa sebesar 41,66%. Aktivitas belajar siswa selama proses pembelajaran menunjukkan peningkatan yang lebih baik. Karena telah memenuhi ketuntasan belajar secara klasikal dan mengalami peningkatan dari siklus I ke siklus II maka dapat disimpulkam bahwa dengan penggunaan model pembelajaran Picture and Picture dapat meningkatkan hasil belajar Seni Budaya siswa pada materi Alat Musik Sederhana di kelas VII.1 SMP Negeri 1 Kisaran Tahun Pelajaran 2017/2018. Kata kunci: picture and picture, alat musik sederhana.